PROSPECTS FOR OIL AND GAS IN THE SOUTHEASTERN PART OF THE DNIEPER-DONETS BASIN - Dudnikov, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In this article the perspectives of oil and gas possibilities in south-eastern part of Dniprovsko-Donetsk depression are considered. This territory was supported unerspectiver on searches of oil and gas fields. However, in 2009 Svyatogirsk’s gas field was discovered there. This fact gives all grounds to revise the traditional opinion about perspectives of south-eastern part of Dniprovsko-Donetsk depression. Within the framework of the article, the state of the geological study and results of the drilling boreholes are considered on Svyatogirska, Slavyanska and Artemivska areas. The main task, which was put before the article, was to show the perspectives of that territory for finding out new deposits of hydrocarbon.